Identification, Prevalence and Intensity of Ectoparasite Protozoa in Litopenaeus vannamei at Intensive and Traditional Shrimp Pond - Ambarwati, Dewi; Pardede, Maria Agustina; Puspita Sari, Putri; Kurnia Agesti, Elmira; Aufa, In’amul; Abdullah, Taufiq; Kumalasari, Ditta Putri (JURNAL MINA SAINS, 2025)
This study investigated the prevalence, diversity, and intensity of ectoparasitic protozoa infecting Litopenaeus vannamei in traditional and intensive shrimp ponds. A total of 25 shrimp from each pond type were examined for the presence of ectoparasitic protozoa. Four parasite species were identified in traditional ponds: Zoothamnium sp., Epistylis sp., Vorticella sp., and Trichodina sp. In contrast, three species (Zoothamnium sp., Epistylis sp., and Vorticella sp.) were found in intensive ponds, with Trichodina sp. absent in the latter. The prevalence of ectoparasitic protozoa was higher in intensive ponds, with 44% of shrimp infected, compared to 8% in traditional ponds. The intensity of infection was also higher in intensive ponds, with an average intensity of 10.27, categorized as medium, compared to an intensity of 5.2 in traditional ponds, categorized as low. These findings suggest that intensive farming conditions may contribute to increased susceptibility to ectoparasitic infections in shrimp. The study emphasizes the importance of monitoring and managing parasite infestations to reduce health risks in shrimp aquaculture systems.